Survei Kondisi Fisik Atlet Dayung Dragon Boat PODSI Provinsi Jambi - Syafitri, Ardhana Nur; Muzaffar, Ahmad; Putra, Anggrawan Janur (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This research aims to evaluate the physical condition of PODSI Jambi Province rowing athletes to enhance performance for upcoming championships. Optimal physical condition is fundamental in rowing, particularly endurance, strength, flexibility, and explosive power. A quantitative descriptive survey method was employed with total sampling of 11 athletes. Measurements included the bleep test (cardiovascular endurance), pull-ups and sit-ups (muscle strength), V-sit and reach (flexibility), and vertical jump (explosive power). Bleep test results showed male athletes in excellent (14%), average (43%), and below average (43%) categories, while female athletes rated good (50%) and average (50%). Pull-up tests: 57% of male athletes rated excellent and 43% good, while all female athletes (100%) rated excellent. Sit-ups: 29% of male athletes rated good, 71% average, while female athletes were in average (75%) and below average (25%) categories. V-sit and reach: 86% of male athletes rated excellent, 14% good, female athletes evenly split between excellent (50%) and good (50%). Vertical jump revealed unsatisfactory results for most athletes. These findings provide a foundation for coaches to develop structured training programs to improve athletes' physical condition and performance.